Predictive implications of decreased CA19‐9 at 8 weeks during nab‐paclitaxel plus gemcitabine for the induction of second‐line chemotherapy for patients with advanced pancreatic cancer. Issue 6 (23rd September 2020) - Iede, Kiyotsugu; Yamada, Terumasa; Kato, Ryo; Ueda, Masami; Tsuda, Yujiro; Nakashima, Shinsuke; Ohta, Katsuya; Matsuyama, Jin; Ikenaga, Masakazu; Tominaga, Shusei
Abstract: Background: Second‐line (2L) chemotherapy after nab‐paclitaxel plus gemcitabine (AG) is important for improving the survival of patients with advanced pancreatic cancer (APC). However, many patients fail to receive 2L chemotherapy because of rapid disease progression. Therefore, early recognition of any ineffectiveness during AG might lead to an increased induction rate of 2L chemotherapy. Aim: We investigated the significance of treatment response at 8 weeks as a predictive factor for the induction of 2L chemotherapy after AG. Methods and results: From January 2015 to January 2019, 41 patients with APC underwent AG as first‐line chemotherapy at our institute. Thirty‐three patients were evaluated at 8 weeks. Sixteen patients (48%) underwent 2L chemotherapy and 17 (52%) underwent no 2L chemotherapy. Clinical features and treatment response at 8 weeks were, retrospectively, compared among patients. Predictive factors for the induction of 2L chemotherapy were analyzed. Patients with an objective response by 8 weeks received 2L chemotherapy more frequently ( P = .026). Decreased CA19‐9 (<50%) at 8 weeks was identified as an independent negative predictive factor for the induction of 2L chemotherapy. Conclusions: Decreased CA19‐9 (<50%) at 8 weeks may indicate the ineffectiveness of AG and signify that a move to 2L chemotherapy may be required without delay.